IDENTIFICATION OF FUNGI TO RED RICE IN TERIAK, BENGKAYANG, WEST BORNEO - ., Mislan; Ramadhan, Tris Haris; Rianto, Fadjar (Jurnal Sains Pertanian Equator, 2019)
Rice (Oryza sativa L.) is a common crop in Indonesia. Kalimantan Barat has a lot of rice germplasm, including local red rice. Some of obstacles that cause a decrease in rice production was plant diseases. There many kind of rice diseases was known. This study aims to determaind rice diseases on red rice in Teriak, Bengkayang. Plant samples for identification took by purposive method and randomized method used to determine the disease progress (incidence and severity). The result of identification showed that there are six diseases in red rice, such as leaf and neck blast, brown leaf spot, narrow brown leaf spot, stackburn, sheath rot and sheath blight. The disease severity calculations on rice leaves was 55,90% - 78,52%, rice stem 0% - 41,48% and panicle of rice 15,19% - 63,70%.Keyword : disease incidence, disease severity, red rice, identification